Influence of age on seven putative prostate tumor markers： a cohort study in Chinese men - Sun, Wei-Gui; Liang, Chao-Zhao; Zheng, Qi-Chuan; Hu, Xiao-Wu; Li, Zhi-Zhen; Wu, Ping (Asian journal of andrology, 2017)
The accuracy and sensitivity of prostate-specific antigen （PSA） for prostate cancer diagnosis is often poor; however, the reasons for its inaccuracy have rarely been investigated, especially with respect to age. In this study, 476 healthy males, aged 10-89 years, were stratified into eight age groups, and levels of seven markers were determined： total PSA （tPSA）, free PSA （fPSA）, %fPSA, isoform [-2]proPSA （p2PSA）, p2PSA/tPSA, %p2PSA, and the prostate health index （PHI）. Both tPSA and fPSA levels increased with age. The tPSA level was highest （1.39 ng m1-1） at 70-79 years; %fPSA was highest （0.57 ng ml-1） at 10-19 years; and %p2PSA was lowest （18.33 ng ml-1） at 40-49 years. Both p2PSA and p2PSA/tPSA had relatively flat curves and showed no correlation with age （P = 0.222）. PHI was a sensitive age-associated marker （P 〈 0.05）, with two peaks and one trough. The coverage rates and radiance graphs of PHI and %p2PSA were more distinctive than those of tPSA and the other markers. In subjects older than 69 years, PHI and %p2PSA both began to decrease, approximately 10 years earlier than the decrease in tPSA. Our results suggest that the clinical diagnosis of prostate cancer using PSA should be investigated more comprehensively based on patient age. Moreover, %p2PSA and PHI could be considered as earlier markers that may be more suitable than PSA alone.